Insurgency and the Shrinking Space for Young Girl Education in the North-East, Nigeria - Foluke, Osunyikanmi Adebukola; Hyacinth, Iwu Nnaoma (European Scientific Journal, ESJ, 2017)
Prior the incursion of Boko Haram insurgency into the social nerve of Nigeria, low level of literacy in the North-East geo-political zone of the country was pervasive and has always been a subject of concern to all stakeholders and the federal government. The Almajiris, a vernacular euphemism for child-beggars, were offered mobile schools. Besides, free and compulsory education were introduced to take school age children off the streets. Of major interest to activists and researcher is the issue of young girl education. The female children had been irresponsibly left behind when western education was introduced to the North. The young girl was neglected for religious, socio-economic and cultural reasons. Expectations of wholistic benefits, therefore, became high when girls finally have opportunity to access Western education. However, Boko Haram insurgency became a clog in the wheel of progress when they began to kidnap girls and women, destroy school properties, and engaged in suicide bombings. The Chibok girls that were kidnapped from a government secondary school in Borno State was a classic case. This paper examines the implications of Boko Haram’s operations and activities on education in the North-East especially on the fragile status of girl child education. Consideration was also given to the far-reaching effect of the insurgency on the economic lives of the affected children. It concludes with a call for government to embark on strategies that will end insurgency and give the young girl a new lease in life.